Imagining Philadelphia : Edmund Bacon and the future of the city - Knowles, Scott Gabriel (EBL-Schweitzer, 2009)
In his 1959 essay "Philadelphia in the Year 2009," Edmund Bacon described a city remade, modernized in time to host the 1976 Bicentennial celebration and Philadelphia World's Fair. Imagining Philadelphia assesses Bacon's vision, discussing what has been accomplished and what might have been.